Answer:
Explanation:
As it is a second order equation, it means that it has two possible answers and they are
and
.
The famous quadratic formula for solving any second order equation is the following:
![x_(1) = (-b + √(b^2 - 4 ac))/(2a)\\x_(2)=(-b - √(b^2 - 4 ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/isbxp31jsmv5eb2y8liyl5d6h066kk1wcv.png)
Where a is the coefficient of
, b is the coefficient of x, and c is the free term. In other words,
![a = 3\\b=4\\c=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/9lbuou1saobs5phs2q0k3td0amlj7mlmdl.png)
as the equation should be in the following form:
![a x^2 + bx+c = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/ptthuihtbz05xoknqep6q3nqnknds5xvh2.png)
Therefore the possible answer should be the following,
![(-4 + √(4^2 - 4*3*(-2)))/(2*3)=(-4 +√(16 + 24))/(6) =(-4 + √(40))/(6)=\\ (-4 + √(4*10))/(6) = (-4 + 2√(10))/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vrenat3f6c4pesay7y6warx3jr39srgmph.png)
![(2*(-2 + √(10)))/(2*3) = (-2 + √(10))/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/7v5ns51keid5cg47nxd61xou2v8g8h78cb.png)
by dividing the numerator and denominator by 2, we can deduce the following,